La tradición helenística y la iconografía del helenismo en Bizancio - Elvira, Miguel Ángel (Antigüedad y Cristianismo, 1990)
The present study analyses the evolution of the components in the iconographie outHne of the Baptism from its Paleochristian origins until its last enrichments in the Late Bizantine Age. It is an attempt to demonstrate up to what point the Bizantine artists, thanks to their profound knowledge of the Graeco-Roman art, could little by little rediscover a system of religious representation which had been used in the Pompeian painting and in the Imperial pagan sarcophagi.